Beyond Trade : The Impact of Preferential Trade Agreements on Foreign Direct Investment Inflows - Medvedev, Denis (World Bank, Washington, DC, 2012)
The author investigates the effects of preferential trade agreements (PTAs) on the net foreign direct investment (FDI) inflows of member countries using a comprehensive database of PTAs in a panel setting. He finds that PTA membership is associated with a positive change in net FDI inflows, and the FDI gains are increasing in the market size of the PTA partners and their proximity to the host country. The author identifies several different channels through which preferential trade liberalization may affect FDI, and confirms that both threshold effects (signing the agreement) and market size effects (joining a larger and faster-growing common market) are important determinants of net FDI inflows, although the latter seem to dominate. The estimated relationship is largely driven by North-South PTAs, and is most pronounced in the late 1990s and early 2000s, the period when the majority of "deep integration" PTAs had been advanced.